TRANSFORMATIONAL LEADERSHIP FOR ENTERING INDUSTRIAL REVOLUTION 4.0 AS COMPARED WITH HUMANE LEADERSHIP AND “U” THEORY - Leo Hutagalung; AGUS PURWANTO; Agustian Budi Prasetya; Rudy Pramono (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2020)
In the beginning of the first twenty years of the 21st century, environmental changes have presented a great challenge for organizational leaders. Demands from within the organization, both individuals, groups, or unions, continued with external pressure organizations require a leader must be able to respond to changing environmental challenges. Humane Leadership described by Gallo and Hlupic (2019) that leadership must move quickly from the level of 1.2.3 to the level of 4 or 5, is an expression that emphasizes the views of experts on transformational leadership so that organizations can survive and develop in era Industrial Revolution 4.0. “U”-Theory introduced Otto Scharmer is a method of change that can be applied in transformational leadership based on self-awareness or contemplation, to release current concessions in total, then move forward creation with a new prototype, until the realization of something new.